Structural and immunological characterization of a glycoconjugate based on the delipidated lipopolysaccharide from a nontypeable Helicobacter pylori strain PJ1 containing an extended d-glycero-d-manno-heptan. (1st February 2018) - Altman, Eleonora; Chandan, Vandana; Harrison, Blair A.; Vinogradov, Evgeny
Abstract: Structural characterization of the lipopolysaccharide (LPS) from a nontypeable Helicobacter pylori strain PJ1 and two corresponding mutants, PJ1 HP1283:cam and PJ1 HP1284:cam, was performed using a combination of NMR and mass spectrometric techniques. It resulted in the core structure that differed significantly from the one proposed previously. Overall architecture of PJ1 LPS was found to be consistent with a structural model described for several other H. pylori strains. It contained a polymer ofd - glycero -d - manno -heptose (dd -Hep) as the O-chain component, linked to α-1, 6-glucan through add -Hep oligosaccharide. H. pylori PJ1 HP1283:cam LPS was missingdd -heptan, terminating with an α-1, 6-glucan chain containing 5–13 glucose residues. LPS of strain PJ1 HP1284:cam was missingdd -Hep from the core and had β-GlcNAc attached directly to O-3 of the inner-coreld -Hep residue. To investigate the role ofdd -heptan in protective immunity, delipidated LPS (dLPS) from strain PJ1 was conjugated to tetanus toxoid (TT) and immunological properties of the resultant glycoconjugate dLPS(PJ1)-TT determined. The dLPS(PJ1)-TT conjugate was immunogenic in mice and rabbits and induced specific and cross-reactive functional antibodies against homologous and heterologous strains of H. pylori . Whole cell indirect ELISA performed on a selected number of H. pylori isolates confirmed that the immune response correlated with the presence of α-1, 6-glucan and was not augmented by thedd -Hep content of these strains. Graphical abstract: Highlights: LPS structures of H. pylori strain PJ1, HP1283:cam and HP1284:cam were determined. The structure of PJ1 LPS was consistent with the structural model of H. pylori LPS. The dLPS(PJ1)-TT conjugate was immunogenic in mice and rabbits. Reactivity of rabbit sera was not affected by DD-Hep content of H. pylori strains.